Subcellular compartmentation of sugar signaling: links among carbon cellular status, route of sucrolysis, sink-source allocation, and metabolic partitioning - Tiessen, Axel; Padilla-Chacon, Daniel (Frontiers in Plant Science, 2013)
Recent findings suggest that both subcellular compartmentation and route of sucrolysis are important for plant development, growth, and yield. Signalling effects are dependent on the tissue, cell type and stage of development. Downstream effects also depend on the amount and localisation of hexoses and disaccharides. All enzymes of sucrose metabolism (e.g. invertase, hexokinase, fructokinase, sucrose synthase, and sucrose 6-phosphate synthase) are not produced from single genes, but from paralogue families in plant genomes. Each paralogue has unique expression across plant organs and developmental stages. Multiple isoforms can be targeted to different cellular compartments (e.g. plastids, mitochondria, nuclei, and cytosol). Many of the key enzymes are regulated by post-transcriptional modifications and associate in multimeric protein complexes. Some isoforms have regulatory functions, either in addition to or in replacement of their catalytic activity. This explains why some isozymes are not redundant, but also complicates elucidation of their specific involvement in sugar signalling. The subcellular compartmentation of sucrose metabolism forces refinement of some of the paradigms of sugar signalling during physiological processes. For example, the catalytic and signalling functions of diverse paralogues needs to be more carefully analysed in the context of post-genomic biology. It is important to note that it is the differential localization of both the sugars themselves as well as the sugar-metabolizing enzymes that ultimately led to sugar signalling. We conclude that a combination of subcellular complexity and gene duplication/subfunctionalization gave rise to sugar signalling as a regulatory mechanism in plant cells.